2020
DOI: 10.1186/s40348-020-00097-2
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokine ratios determine the clinical course of febrile neutropenia in children receiving chemotherapy

Abstract: Background: Febrile neutropenia is a common and serious complication during treatment of childhood cancer. Empirical broad-spectrum antibiotics are usually administered until neutrophil cell count recovery. It was the aim of this study to investigate cytokine profiles as potential biomarkers using in-vitro sepsis models to differentiate between distinct clinical courses of febrile neutropenia (FN). Methods: We conducted an observational study in FN episodes of pediatric oncology patients. Courses of neutropeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…In other diseases, the ratio between pro-and anti-inflammatory cytokines is estimated to be more significant than the absolute value of individual cytokines. 13,[23][24][25][26] In the hydrocephalus group on days 7, 14, and 21, our study revealed a significant imbalance in the IL-1β/IL-10 ratio, favoring the pro-inflammatory cytokine. In the hydrocephalus groups, the ratios of IL-6/IL-10 and TNF-α/IL-10 also shifted in favor of a pro-inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…In other diseases, the ratio between pro-and anti-inflammatory cytokines is estimated to be more significant than the absolute value of individual cytokines. 13,[23][24][25][26] In the hydrocephalus group on days 7, 14, and 21, our study revealed a significant imbalance in the IL-1β/IL-10 ratio, favoring the pro-inflammatory cytokine. In the hydrocephalus groups, the ratios of IL-6/IL-10 and TNF-α/IL-10 also shifted in favor of a pro-inflammatory status.…”
Section: Discussionmentioning
confidence: 99%